과공정 Al-Si 합금의 마모 거동과 기계적 성질에 미치는 TiC와 AlN의 영향 - 김용진; Yong Jin Kim; 박익민; Ik Min Park; 박용호; Yong Ho Park; 최진명; Jin Myung Choi; 주승환; Seung Hwan Ju (대한금속·재료학회지, 48(11), 2010)
In this study, the effect of the reinforcement on the wear behaviour and mechanical properties of hypereutectic Al-Si alloys was investigated. The Gas atomized hypereutectic Al-20Si alloy powders were mixed with 1, 3, and 5 wt.% AlN and TiC ceramic particles and consolidated by hotpress. The Al-20Si powder has both finely dispersed primary Si phases and eutectic structures. The Al-20Si-AlN, TiC composites showed that the reinforcements were distributed along the boundary of the Al-20Si alloy. The UTS increased with increasing the AlN, TiC contents. At a lower load, with an increasing weight fraction of reinforcements, the wear rate decreased in both composites and the wear mechanism was adhesive wear. At a higher load, the shape of the debris changes the mechanism of the AlN composites to abrasive-adhesion wear and this resulted in an increase of the wear rate.